A Novel Summarization-based Approach for Feature Reduction Enhancing Text Classification Accuracy - Rahamat Basha, S.; Keziya Rani, J.; Prasad Yadav, J. J. C. (Engineering, Technology & Applied Science Research, 2019)
Automatic summarization is the process of shortening one (in single document summarization) or multiple documents (in multi-document summarization). In this paper, a new feature selection method for the nearest neighbor classifier by summarizing the original training documents based on sentence importance measure is proposed. Our approach for single document summarization uses two measures for sentence similarity: the frequency of the terms in one sentence and the similarity of that sentence to other sentences. All sentences were ranked accordingly and the sentences with top ranks (with a threshold constraint) were selected for summarization. The summary of every document in the corpus is taken into a new document used for the summarization evaluation process.